2013
DOI: 10.1186/1471-2148-13-78
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary divergence of the swim bladder nematode Anguillicola crassus after colonization of a novel host, Anguilla anguilla

Abstract: BackgroundAnguillicola crassus, a swim bladder nematode naturally parasitizing the Japanese eel, was introduced about 30 years ago from East Asia into Europe where it colonized almost all populations of the European eel. We conducted a common garden experiment under a reciprocal transfer design infecting both European and Japanese eels with populations of A. crassus from Germany, Poland and Taiwan. We tested, whether differences in infectivity, developmental dynamics and reproductive output between the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 45 publications
5
44
1
1
Order By: Relevance
“…It was recently shown that genetically fixed changes in infectivity and developmental traits separate European A. crassus from their Taiwanese conspecifics [10]. The selective pressure of the novel host (European eel), not the genetic drif, was thus considered to have modified the developmental features in the European strains of A. crassus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently shown that genetically fixed changes in infectivity and developmental traits separate European A. crassus from their Taiwanese conspecifics [10]. The selective pressure of the novel host (European eel), not the genetic drif, was thus considered to have modified the developmental features in the European strains of A. crassus.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a series of experiments infecting A. japonica and A. anguilla with A. crassus originating from Germany, Poland and Taiwan, as described in [10].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular European nematodes had an accelerated development compared to Asian nematodes (Weclawski et al, 2013). In the same experiment two European isolates from Poland were found to be diverged from those from Germany and Taiwan for morphological traits used to differenciate Anguillicola species (Weclawski et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…This is unexpected, as large morphological differences are observed between nematodes from different host species in the wild (Münderle et al, 2006) and in laboratory infections (Knopf and Mahnke, 2004;Weclawski et al, 2013;Weclawski et al, 2014). A possible reason might be that nematodes are influenced by and respond to the host immune system only during the larval stages migrating through tissues.…”
Section: Differential Gene Expression Between Sexes Is Negatively Cormentioning
confidence: 99%